Penerapan Metode Pembelajaran Discovery Learning Menggunakan Aplikasi Quizizz untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran TIK di SMPN 1 Lebakwangi - Yasa, Regita Amelia; Zakaria, Yoyo (Indo-MathEdu Intellectuals Journal, 2025)
This study was motivated by the low learning outcomes of students in Information and Communication Technology (ICT) at SMPN 1 Lebakwangi due to the use of conventional methods that are passive and lack interactivity. To address this issue, the Discovery Learning method was implemented with the assistance of the Quizizz application as an interactive, enjoyable, and educational game-based platform capable of providing immediate feedback. The objective of this study is to determine students' learning outcomes before and after the implementation of Discovery Learning assisted by Quizizz, as well as to analyze its impact on improving learning outcomes. The research method used a quasi-experimental design with a One Group Pretest-Posttest design. The research sample consisted of 31 ninth-grade students from Class IX A, selected using purposive sampling. Data were collected through observation, learning achievement tests (pretest and posttest), and student response questionnaires, then analyzed using normality, homogeneity, and t-tests with the help of SPSS version 26. The results of the study showed a significant increase in the average learning achievement of students. Student responses were also very positive; they felt more active, motivated, and able to understand the material more easily